The Storytelling as a Pedagogical Tool in Qur'anic Education: Effects on Students' Intrinsic Motivation - Muhaimin; Devin Puspita MQ (Al-Qalam Institue, 2026)
This study investigates the effect of storytelling in Qur’anic instruction on students' intrinsic learning motivation in primary education. A quantitative approach with an ex post facto correlational design was employed, involving 33 sixth-grade students selected through total sampling. Data were gathered using a validated Likert-scale questionnaire (α = 0.86). Statistical analyses, including descriptive statistics, assumption testing, Pearson correlation, and simple linear regression, were conducted using SPSS 26.00. The results show a very strong and statistically significant relationship between storytelling and intrinsic motivation (r = 0.878, p < 0.05), with storytelling accounting for 77.1% of the variance in students' intrinsic motivation (R² = 0.771). These findings suggest that storytelling serves as a powerful pedagogical tool that enhances students' internal engagement in learning. Theoretically, the study supports Self-Determination Theory, demonstrating that narrative-based instruction promotes meaningful engagement, emotional connection, and intrinsic motivation. Practically, the results emphasize the value of incorporating storytelling in Qur'anic instruction to foster engaging, context-driven, and value-oriented learning environments.